RDB2OWL: AN IMPROVED METHOD FOR CONVERTING RELATIONAL DATABASES INTO OWL - Phạm Thị Thu Thúy (Tạp chí Khoa học Đại học Đà Lạt, 2017)
One of the biggest advantages of the Semantic web is to describe data with a well-defined meaning and link between data by using the OWL (Web Ontology Language). Today most data are stored in relational databases. In order to reuse the data on the Semantic Web, there is a need for transforming the data stored in relational databases into the form of OWL Ontology. Some approaches have been proposed; however, most of their transformation rules have not been complete. This paper proposes some improved rules for transforming relational database into OWL Ontology. Most of all, all the steps in RDB2OWL are done automatically without any user intervention.